KORELASI ANTARA MOTIVASI PETANI MENGIKUTI KOPERASI DAN KEWIRAUSAHAAN DALAM USAHATANI DENGAN PERSEPSI TERHADAP KEBERHASILAN KOPERASI - Odilia Mery Indriana; Liska Simamora (Universitas Galuh, 2023)
Entrepreneurial activities in Indonesian agriculture, especially food crops, are still carried out traditionally. It is different from that in Mlatiharjo Village, Gajah District, Demak Regency, where people who work as rice farmers who jointly built the Citra Kinaraya Multi-Business Cooperative in which there are business activities such as rice cultivation, rice production and rice marketing using a touch of innovation and supported by the use of modern technology so as to produce quality and competitive rice which is named Beras Melati. In developing these business activities, farmers will not be separated from farming motivation and entrepreneurship within themselves so that they can build a business activity that can continue to survive in the midst of advances in agricultural science and technology. The purpose of this study was to determine the relationship between farmers' motivation to join cooperatives and entrepreneurship in farming with perceptions of the success of cooperatives. This research uses a quantitative descriptive approach. The research sample was taken by purposive sampling method and using Rank Spearman correlation analysis tool. The results showed that all independent variables had a positive and significant correlation with perceptions of cooperative success. The motivation variable of farmers joining cooperatives has a strong relationship with cooperative success while entrepreneurship in farming seen from the innovation variable has a weak relationship, the risk-taking variable has a moderate relationship and managerial ability also has a moderate relationship with business success in cooperatives.